COMPARISON BETWEEN ISO 281:1990 AND ISO 281:2007 CALCULATION METHOD FOR ROLLING BEARING LIFE - JIANG YuXiao; LIU ShaoJun (Jixie qiangdu, 2015)
Comparative analysis of International Standards Organization standard（ ISO） 281: 1990（ the equivalent of GB /T6391- 2003） and ISO 281: 2007（ the equivalent of GB / T6391- 2010） Calculation Method for Rolling Bearing Life was conducted. Differences between the meaning and selection of Life modification factor,as well as their effects on Rolling Bearing Life,were analyzed through calculations. The study indicates that the ISO 281: 2007 introduces the Life modification factor for systems approach,and the factor considers not only the two factors of the ISO 281: 1990 but also the fatigue stress limit of the bearing steel and the contamination in lubricant,which makes it easy and more reliable to estimate the influence of lubrication and contamination on bearing life.